(untitled) (Journal of Finance, Business and Management Studies, 2021)
The COVID-19 outbreak has seen significant changes to lives when authorities imposed several regulations to curb transmission. These include movement restrictions, social imprisonment, closure of economic and social sectors including the education sector. One of the groups of students affected by the COVID-19 pandemic is postgraduate students. This study was conducted involving postgraduate students in one of the institutions of higher learning in the north of peninsular Malaysia. In August 2021, a total of 47 postgraduate students were involved in an online survey using Google Form. The students were found to have devices for online learning using Google Meet, Zoom, Webex, and Youtube. Students also reported that they faced difficulty adjusting as well as financial stress. The students also reported that they did not face relationship problems and perceived that the university did support postgraduate students. Among the things that worry students are tuition fees, concerns about being infected with the COVID-19 epidemic, as well as the extension of the study period. Students also hope to use the facilities on campus more often and be appointed as teaching assistants.